LASER SCANNING FOR THE GEOMETRIC STUDY OF THE ALCÁNTARA BRIDGE AND CORIA CATHEDRAL - J. De Matías (Escuela Politécnica, Universidad de (Copernicus Publications, 2018)
The conservation of built heritage is becoming increasingly important, and may even be an obligation for future generations. Techniques must therefore be developed to help document heritage and thus improve knowledge and conservation. The terrestrial laser scanning technique allows a massive capture of points of an object. Among its main applications are to obtain geometries of historic buildings and monuments, allowing the documentation of their heritage. But this technique also facilitates other very important information for the conservation of the monument in question from the same data set: the damage it presents. We can, therefore, also document the geometry of the object by making a survey of the damage it presents at the moment of data collection. The cracks and their layout and trajectory can be observed, allowing measurements to be made to assess necessary conservation measures. Given that the apertures of the same crack at different points in historical structures often vary by several centimeters, it is also important to know the extent of the damage along its entire path, and whether there is any relative motion between the two sides of the crack. This communication presents the application of laser scanning in the Alcántara Bridge and Coria Cathedral, both in the province of Cáceres (Spain). It outlines the criteria used for scanning both monuments: selection of placements, recording technique, errors between placements and the elimination of residual points. Once the mesh had been obtained, the information on the damage presented by these monuments was analysed, describing, characterizing and contrasting them with data taken in the field.